1990
DOI: 10.1115/1.2910390
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study on Natural Convection in Isotropic and Anisotropic Porous Channels

Abstract: This paper is an analytical study on natural two-dimensional convection in horizontal rectangular channels filled by isotropic and anisotropic porous media. The channel walls, assumed to be impermeable and perfectly heat conducting, are nonuniformly heated to establish a linear temperature distribution in the vertical direction. We derive the critical Rayleigh numbers for the onset of convection and examine the steady flow patterns at moderately supercritical Rayleigh numbers. The stability properties of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 0 publications
6
66
0
1
Order By: Relevance
“…Haugen and Tyvand [9] gave a mathematical analysis to confirm that only axisymmetric mode of convection is prevalent in slendercylinder limit for perfectly heat-conducting side wall. The smooth relation between Ra c and a was found by Nilsen and Storesletten [10] for thermal convection in a twodimensional box with conducting walls and also verified by Rees and Lage [11] for natural convection in a vertical porous insulation layer. The case at Bi=10 4 also presents a nearly smooth relation between Ra c and a because large Bi corresponding to perfectly heat-conducting case.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Haugen and Tyvand [9] gave a mathematical analysis to confirm that only axisymmetric mode of convection is prevalent in slendercylinder limit for perfectly heat-conducting side wall. The smooth relation between Ra c and a was found by Nilsen and Storesletten [10] for thermal convection in a twodimensional box with conducting walls and also verified by Rees and Lage [11] for natural convection in a vertical porous insulation layer. The case at Bi=10 4 also presents a nearly smooth relation between Ra c and a because large Bi corresponding to perfectly heat-conducting case.…”
Section: Resultsmentioning
confidence: 70%
“…The eigenvalue problem for temperature perturbation composed of (18), (19), (10) and (22) is solved by using separation of variables. We assume two eigen-functions corresponding to the two Helmholtz equations in the form …”
Section: Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the phenomena mentioned above are also realized in this problem, but our study is motivated mainly by nontrivial facts observed here and previously not yet 20 encountered in the problems of mathematical physics. This is the result of the action of cosymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the condition of a finite lateral width of the channel was analysed as well. The case of a horizontal porous channel with rectangular cross-section was studied by Sutton (1970), Beck (1972), and further explored by Nilsen and Storesletten (1990).…”
Section: Introductionmentioning
confidence: 99%